A new pseudoscorpion genus (Garypinoidea: Garypinidae) from the Eocene supports extinction and range contraction in the European paleobiota - Stanczak, Nova; Harvey, Mark S.; Harms, Danilo; Hammel, Jörg U.; Kotthoff, Ulrich; Loria, Stephanie (PeerJ, Inc., 2023)
During the Paleogene, the Holarctic experienced drastic climatic oscillations, including periods of extensive glaciation. These changes had a severe impact on both the flora and fauna causing widespread extinction and range shifts with some taxa retreating to refugia in the Mediterranean Basin. Here we provide evidence for this hypothesis using fossils from the pseudoscorpion family Garypinidae Daday, 1889 (Arachnida: Pseudoscorpiones). This family comprises 21 extant genera from all continents except Antarctica but is restricted to low mid-latitudes (<44°N) in the Northern Hemisphere. We provide the second record of garypinids from the European succinite ambers of the Eocene by describing the first extinct genus in Garypinidae, Baltamblyolpium gen. nov., which includes two species: Baltamblyolpium gizmotum sp. nov. from Baltic amber and Baltamblyolpium grabenhorsti sp. nov. from Bitterfeld amber. The new genus exhibits a morphology that closely resembles Neoamblyolpium Hoff, 1956 from western North America and the genus Amblyolpium Simon, 1898, which is widespread but includes taxa restricted to Mediterranean refugia in Europe. The discovery of a new fossil genus of Garypinidae from Europe confirms that the family was found at more northerly latitudes during the Eocene, however, extinction and range contraction resulted in their present-day relictual distribution in southern Europe like many other lineages that once thrived in the European “Baltic amber forest” of the Eocene.